Theoretical Study of the Impact of Al, Ga and In Doping on Magnetization, Polarization, and Band Gap Energy of CuFeO2 - A. T. Apostolov; I. N. Apostolova; J. M. Wesselinowa (Applied Sciences, 2025)
We have conducted a first-time investigation into the multiferroic properties and band gap behavior of <semantics>CuFeO2</semantics> doped with Al, Ga, and In ions at the Fe site, employing a microscopic model and Green’s function formalism. The tunability of the band gap across a broad energy spectrum highlights the potential of perovskite materials for advanced applications, including photovoltaics, photodetectors, lasers, light-emitting diodes, and high-energy particle sensors. The disparity in ionic radii between the dopant and host ions introduces local lattice distortions, leading to modifications in the exchange interaction parameters. As a result, the influence of ion doping on various properties of <semantics>CuFeO2</semantics> has been elucidated at microscopic level. Our findings indicate that Al doping enhances magnetization and reduces the band gap energy. In contrast, doping with Ga or In results in a decrease in magnetization and an increase in band gap energy. Additionally, it is demonstrated that ferroelectric polarization can be induced either via external magnetic fields or by Al substitution at the Fe site. The theoretical results show good qualitative agreement with experimental data, confirming the validity of the proposed model and method.